Vibrational and rotational spectral data for possible interstellar detection of AlH3OH2, SiH3OH, and SiH3NH2. Issue 2 (22nd September 2021) - Watrous, A G; Westbrook, B R; Davis, M C; Fortenberry, Ryan C
ABSTRACT: This work provides the first full set of vibrational and rotational spectral data needed to aid in the detection of AlH3 OH2, SiH3 OH (silanol), and SiH3 NH2 (silylamine) in astrophysical or simulated laboratory environments through the use of quantum chemical computations at the CCSD(T)-F12b level of theory employing quartic force fields for the three molecules of interest. Previous work has shown that SiH3 OH and SiH3 NH2 contain some of the strongest bonds of the most abundant elements in space. AlH3 OH2 also contains highly abundant atoms and represents an intermediate along the reaction pathway from H2 O and AlH3 to AlH2 OH. All three of these molecules are also polar with AlH3 OH2 having the largest dipole of 4.58 D and the other two having dipole moments in the 1.10–1.30 D range, large enough to allow for the detection of these molecules in space through rotational spectroscopy. The molecules also have substantial infrared intensities with many of the frequencies being over 90 km mol −1 and falling within the currently uncertain 12–17 μm region of observed infrared spectra. The most intense frequency for AlH3 OH2 is ν 9 that has an intensity of 412 km mol −1 at 777.0 cm −1 (12.87 μm). SiH3 OH has an intensity of 183 km mol −1 at 1007.8 cm −1 (9.92 μm) for ν 5, and SiH3 NH2 has an intensity of 215 km mol −1 at 1000.0 cm −1 (10.00 μm) for ν 7 .